1969
DOI: 10.1177/001440296903600304
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Blind Students through Active and Passive Listening

Abstract: Studies were conducted comparing learning achieved by blind students at different grade levels for 3 types of material presented at normal and compressed rates under conditions of active and passive listening. Findings of the research lend support to the theory that active participation in the listening process results in greater learning. A secondary finding was that comprehension of uncompressed material was superior to comprehension of compressed material under conditions of motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

1974
1974
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…In the 1950s, the term active participation while learning became popular in politics for conflict resolution (Bauer, 1958) and education for exceptional children (Bishton, 1956). The term active learning emerged in the 1960s to address the learning needs of blind patients (Nolan & Morris, 1969) and to change traditional teaching methods to involve student participation (Lumsden, 1969). Some publications in the 1970s from nursing, adult learning, and higher education encouraged teachers to use student-centered learning strategies.…”
Section: Methodsmentioning
confidence: 99%
“…In the 1950s, the term active participation while learning became popular in politics for conflict resolution (Bauer, 1958) and education for exceptional children (Bishton, 1956). The term active learning emerged in the 1960s to address the learning needs of blind patients (Nolan & Morris, 1969) and to change traditional teaching methods to involve student participation (Lumsden, 1969). Some publications in the 1970s from nursing, adult learning, and higher education encouraged teachers to use student-centered learning strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Alan yazında sınırlı sayıda yapılan çalışmada, total düzeyde görme yetersizliği olan öğrencilerin, dinleme materyallerini ya da öğretmenlerinin ders anlatımlarını dinlerken pasif dinleyici davranışları gösterdikleri vurgulanmaktadır (Nolan & Morris, 1969). Öte yandan alan uzmanları, total düzeyde görme yetersizliği olan öğrencilerin, dinleme becerisini nasıl daha etkili kullanacağı ve dinledikleri materyalleri anlamaları için neler yapmaları gerektiği konusunda sınırlı bilgiye sahip olduklarını ifade etmektedirler (Tuncer & Altunay, 2006;Yalçın & Altunay Arslantekin, 2019).…”
Section: Introductionunclassified
“…Öğrencilere dinleme ve dinlediğini anlamaya yönelik yapılacak sistemli öğretim etkinliklerinin yanı sıra alan yazında öğrencilerin aktif dinleme davranışlarını sergilemesinde bazı faktörlerin etkili olduğu da savunulmaktadır. Genel anlamda bu faktörler; öğrenci ve materyal özelliklerine göre farklılıklar göstermektedir (Nolan & Morris, 1969). Görme yetersizliği olan öğrenciler açısından spesifik olarak ele alındığında, öğrencinin problem davranışının olup olmaması, motivasyonu, dinleme stratejilerini kullanma durumu gibi etmenlerden bahsedilebilir.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The principle has been applied to aural study in an effort to improve the learning efficiency of blind students. Nolan & Morris (1969) found that blind high school students retained more information from literature and social science texts when given breaks for mental review or for notetaking, than when they listened passively to the continuous text. Brothers (1970) established that it was indeed the activity in the intervals which facilitated learning, rather than the breaks themselves, or the shortening of the text segments.…”
mentioning
confidence: 94%